Tyrosine kinase inhibitors in treatment of fibrous histiocytoma - Maur, D.; Panou, C.; Valachis, A.; Kamposioras, K.; Tsali, L. (Experimental Oncology, 2009)
Aim: To describe potential beneficial effects of tyrosine kinase inhibitor in the treatment of unresectable/metastatic fibrous histiocytoma. Methods: We report a case of advanced stage fibrous histiocytoma with locally recurrent disease plus lung and bone metastatic deposits. Patient was treated with the tyrosine kinase inhibitor sunitinib. Results: Treatment with Sunitinib resulted in disease stabilization in the regional lesion and in good partial response for metastatic foci (reduction in number and size). After 13 months of treatment the patient is doing well with no tumor progression. Conclusions: This case appears to be one of the first documentations of beneficial effect and potential long-term benefit of TKIs in the treatment of fibrous histiocytoma.